Antibiotic resistance and clonal diversity of invasive Staphylococcus aureus in the rural Ashanti Region, Ghana. Issue 1 (December 2016) - Dekker, Denise; Wolters, Manuel; Mertens, Eva; Boahen, Kennedy; Krumkamp, Ralf; Eibach, Daniel; Schwarz, Norbert; Adu-Sarkodie, Yaw; Rohde, Holger; Christner, Martin; Marks, Florian; Sarpong, Nimako; et al.
Abstract Background Staphylococcus aureus is among the most common pathogens isolated from blood cultures in Ghana; yet the epidemiology of blood infections in rural settings is poorly described. This study aims to investigate antimicrobial susceptibility and clonal diversity ofS. aureus causing bloodstream infections in two hospitals in the Ashanti Region, Ghana. Methods Blood cultures were performed for all febrile patients (≥37.5 °C) on hospital admission. Antibiotic susceptibility testing forS. aureus isolates was carried out by the VITEK 2 system. Multiplex polymerase chain reaction (PCR) was used to detectS. aureus -specificnuc gene, Panton-Valentine leukocidin (PVL), and methicillin-resistantS. aureus (MRSA)-specificmecA andmecC genes. The population structure ofS. aureus was assessed byspa typing. Results In total, 9, 834 blood samples were cultured, out of which 0.6% (n  = 56) were positive forS. aureus. Multidrug resistance (MDR) was detected in 35.7% (n  = 20) of theS. aureus strains, of which one was a MRSA. The highest rate of antibiotic resistance was seen for commonly available antibiotics, including penicillin (n  = 55; 98.2%), tetracycline (n  = 32; 57.1%) and trimethoprim/sulfamethoxazole (n  = 26; 46.4%). Of allS. aureus strains, 75.0% (n  = 42) carried the PVL-encoding genes. We found 25 differentspa types with t355 (n  = 11; 19.6%), t314 (n  = 8; 14.3%), t084 (n  = 8; 14.3%) and t311 (n  = 5; 8.9%) being predominant. Conclusion The study exhibited an alarmingly large level of antibiotic resistance to locally available antibiotics. The frequency of genetically diverse and PVL-positive methicillin-sensitiveS. aureus (MSSA) was high and could represent a reservoir for the emergence of virulent PVL-positive MRSA clones.